ANALISIS MAKNA ILUSTRASI PERMAINAN BALOK JENGA PADA POSTER WWF - Claudya Alvita (TUTURRUPA, 2021)
Research on the Meaning Analysis of Jenga Block Game Illustration on WWF Poster aims to reveal the meaning or message to be conveyed from the illustration image. This research is a qualitative research. The research was conducted on the illustration of the Jenga block game on the WWF poster, data collection was carried out by observation, namely observing and analyzing the illustrations in the poster based on Roland Barthes' semiotic theory. The results of this study indicate that the Jenga beam illustration on the WWF poster tells about the composition of the ecosystem and human actions that disturb its balance. The illustration of the Jenga block game on the WWF poster also illustrates the condition of a vulnerable ecosystem and aims to remind humans to maintain the integrity of the ecosystem.